Boosting Segment Anything Model Towards Open-Vocabulary Learning - Han, Xumeng; Wei, Longhui; Yu, Xuehui; Dou, Zhiyang; He, Xin; Wang, Kuiran; Sun, Yingfei; Han, Zhenjun; Tian, Qi (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
The recent Segment Anything Model (SAM) has emerged as a new paradigmatic vision foundation model, showcasing potent zero-shot generalization and flexible prompting. Despite SAM finding applications and adaptations in various domains, its primary limitation lies in the inability to grasp object semantics. In this paper, we present Sambor to seamlessly integrate SAM with the open-vocabulary object detector in an end-to-end framework. While retaining all the remarkable capabilities inherent to SAM, we boost it to detect arbitrary objects from human inputs like category names or reference expressions. Building upon the SAM image encoder, we introduce a novel SideFormer module designed to acquire SAM features adept at perceiving objects and inject comprehensive semantic information for recognition.In addition, we devise an Open-set RPN that leverages SAM proposals to assist in finding potential objects.Consequently, Sambor enables the open-vocabulary detector to equally focus on generalizing both localization and classification sub-tasks.Our approach demonstrates superior zero-shot performance across benchmarks, including COCO and LVIS, proving highly competitive against previous state-of-the-art methods.We aspire for this work to serve as a meaningful endeavor in endowing SAM to recognize diverse object categories and advancing open-vocabulary learning with the support of vision foundation models.